Doomsday for the euro area: Causes, variants and consequences of breakup - Ansgar Belke; Florian Verheyen (International Journal of Financial Studies, 2013)
In this paper we describe the genesis of a doomsday scenario and discuss potential causes and motivations for a breakup of the euro area. For this purpose, we differentiate between the departure of weak and strong countries, and examine the impact of the reintroduction of a national currency on domestic debt, the domestic banking sector, EU membership and the freedom of trade. We also briefly analyze the social and political costs of the accompanying social disorder.
Keywords: E58; F33; F41; 330; banking crisis; debt crisis; exchange rates; euro; optimum currency area; secession